ANALISIS TANTANGAN GURU IPA SMP DI INDONESIA DALAM MENERAPKAN PEMBELAJARAN IPA TERINTEGRASI STEM - Niken Kartika Candra; Clarissa Jeanny; Mochamad Setiawan; Nur Ahmad (Pendidikan Fisika FKIP UNEJ, 2022)
The implementation of STEM in Indonesia is still recently implemented before it was only a discussion of articles because there were challenges for teachers in its application. Therefore, this research was conducted to map all articles published online with the theme of implementing STEM education in Indonesia. This research method is carried out by summarizing articles from various reputable scientific journals. The next step in processing the reference sources obtained, namely the stage of collecting data, analyzing data, inferring the content of the data, and responding to the data scientifically. Five articles discussing STEM Implementation in Indonesia were selected using journal data from the keywords